Rebuilding Germany The Creation of the Social Market Economy, 1945-1957 - Van Hook, James C. 1968- (Cambridge Univ. Press, 2004)
Cover -- Half-title -- Title -- Copyright -- Dedication -- Contents -- Preface -- List of Abbreviations -- Introduction -- 1 Planning for Reconstruction -- planning and reality -- revisions and reality -- socialism in the western zones -- conclusion -- 2 The Future of the Ruhr -- the evolution of british socialization policy -- the spd, the french, and the control commission -- clash in london, clash in north rhine-westphalia -- conclusion -- 3 High Hopes and Disappointment: The SPD and the Planning Regime, 1945-47 -- creating the ZENTRALAMT FÜR WIRTSCHAFT -- SELBSTVERWALTUNG DER WIRTSCHAFT -- the bizone, the spd, and economic politics -- the points system and economic crisis in 1947 -- the withdrawal of the spd from the administration -- conclusion -- 4 Ludwig Erhard, the CDU, and the Free Market -- konrad adenauer's cdu -- johannes semler -- ludwig erhard and the "guiding principles" -- from inflation to düsseldorf -- conclusion -- 5 Free Markets, Investment, and the Ruhr -- problems of the reforms -- payments crisis -- the korean war economic crisis in germany -- the intervention of industry -- conclusion -- 6 The Social Market Economy and Competition -- the josten draft -- the problem of heavy industry -- competition and the anticartel law, 1950-57 -- Conclusion -- Bibliography -- Unpublished Primary Sources -- Germany -- Bundesarchiv, Coblenz -- BDI Haus, Institut der deutschen Wirtschaft, Cologne -- Friedrich Ebert Foundation, Bonn -- Archiv für Christlich-Demokratische Politik, St. Augustin -- Rheinisch-Westfälisches-Wirtschaftsarchiv, Cologne -- Stiftung-Bundeskanzler-Adenauerhaus, Rhöndorf -- Ludwig Erhard Foundation, Bonn -- Great Britain -- Churchill Archives, Cambridge -- London School of Economics - London -- Public Record Office, Kew -- United States -- National Archives and Records Administration, College Park, Maryland.